2010
DOI: 10.1182/blood-2010-01-266536
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state generation of mucosal IgA+ plasmablasts is not abrogated by B-cell depletion therapy with rituximab

Abstract: IntroductionPlasmablasts are an immediate product of B-cell activation that home either to the bone marrow or to the mucosa to secrete antibody as terminally differentiated plasma cells. [1][2][3] In healthy persons, B cells and antibodies protect from pathogens, whereas loss of immunologic tolerance and malignant transformation result in the generation of autoreactive B cells and autoantibody production and development of lymphoma, respectively. Direct targeting of B cells by the chimeric anti-human CD20 anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 47 publications
3
79
0
Order By: Relevance
“…In a study of patients with active SLE given rituximab, clonally related B‐cells were found to be persistent in all seven patients, but not found in any of the four age‐matched healthy controls 53. This is consistent with preferential depletion of naïve and CD20 high B‐cells, with the surviving B‐cell population consisting of CD20 low B‐cells, including plasmablasts60 and mucosal IgA + plasmablasts that are not removed by B‐cell depletion therapy. As yet, however, there has been no large‐scale analysis of BCR usage in a large number of patients on ‘standard‐of‐care’ non‐B‐cell depleting therapy.…”
Section: Slementioning
confidence: 65%
See 1 more Smart Citation
“…In a study of patients with active SLE given rituximab, clonally related B‐cells were found to be persistent in all seven patients, but not found in any of the four age‐matched healthy controls 53. This is consistent with preferential depletion of naïve and CD20 high B‐cells, with the surviving B‐cell population consisting of CD20 low B‐cells, including plasmablasts60 and mucosal IgA + plasmablasts that are not removed by B‐cell depletion therapy. As yet, however, there has been no large‐scale analysis of BCR usage in a large number of patients on ‘standard‐of‐care’ non‐B‐cell depleting therapy.…”
Section: Slementioning
confidence: 65%
“…Within the IgG memory B‐cell population, there was no significant change in IGHV, D or J gene usage, CDR3 region length or charge before and after therapy. However, the frequencies of clonally expanded IgG memory B‐cells significantly increased after therapy, corresponding to preferential depletion of naïve and CD20 high B‐cells, with the remainder low‐level B‐cell population consisting of CD20 low B‐cells, including plasmablasts 60. However, further studies are required to determine the differences between therapies and if there are B‐cell repertoire features associated with remission and long‐term outcome.…”
Section: Msmentioning
confidence: 99%
“…Early recovery in serum IgA levels suggests that the IgA plasma cell pool was rapidly replenished. It has previously been reported that circulating IgA+ plasmablasts can remain detectable early after rituximab, suggesting resistance to depletion of switched IgA+ precursor B cells, likely in the mucosal microenvironment and/or early regeneration 52. Serum IgG levels, despite showing a longer “lag” when compared with the recovery of serum IgA levels, was apparently also sustainable, attaining pretreatment levels in most patients by 12 months after rituximab.…”
Section: Discussionmentioning
confidence: 85%
“…Notably, another recent report90 demonstrated that precursors of CD19+/IgA+ plasma blasts, which are continuously circulating in ‘steady state’,91 were not completely depleted by rituximab. While there was no relation to RA disease activity, these plasma blasts can produce protective mucosal IgA consistent with the lack of increased mucosal infections during rituximab treatment.…”
Section: Cellular Biomarkersmentioning
confidence: 98%